Social identity analysis the Buttonscarves community in building brand loyalty - Nurul Mustaqimmah; Bagasati, Lintang Arum (Penerbit Universiti Kebangsaan Malaysia, 2024)
Social Identity is part of the self concept that comes from experience and knowledge of individuals when they are in a particular social group. The association of individuals in the community unknowingly makes community members loyal to certain brands, one of which is the Buttonscarves community. This study wanted to see how social identity can build community members' loyalty to the Buttonscarves brand. Through the theory of social identity proposed by Jackson & Smith about social identity that underlies Four dimensions where a person has perception in the context of intergroup, attraction in groups, interrelated beliefs and depersonalization that produce brand loyalty proposed by Alfares are positive behavior towards the brand, repeat purchases, satisfaction, liking, commitment, trust and transition costs. The results of this study show that the identity formed in the Buttonscarves community can increase brand loyalty to the Buttonscarves brand. Each individual in the community has the same goal so as to form a social identity so as to exclude negative issues from outsiders. The uniqueness, economic value and reputation that Buttonscarves have is able to meet the symbolic needs of community members. This phenomenon can be used by business practitioners as a marketing communication model to achieve brand loyalty from consumers.